Dimeric and trimeric catenation of giant chiral (8+12) imine cubes Driven by weak supramolecular interactions [data] - Benke, Bahiru P.; Kirschbaum, Tobias; Graf, Jürgen; Gross, Jürgen H.; Mastalerz, Michael (Universität, 2022)
Mechanically interlocked structures, such as catenanes or rotaxanes are fascinating synthetic targets and some are used for molecular switches and ...